Do wealthy farmers implement better agricultural practices? An assessment of implementation of Good Agricultural Practices among different types of independent oil palm smallholders in Riau, Indonesia - Jelsma, I.; Woittiez, Lotte Suzanne; Ollivier, J.; Dharmawan, A.H. (Elsevier, 2019)
Palm oil has become a leading vegetable oil over the past 30 years and smallholder farmers in Indonesia, with more than 12 million hectare the world’s largest producer of palm oil, have massively engaged in oil palm (Elaeis guineensis) cultivation. In Sumatra, where more than 60% of Indonesian palm oil is cultivated, smallholders currently cover roughly 50% of the oil palm area. The rapid expansion of palm oil however did not happen without controversy. In current efforts by the Indonesian government, NGO's and private sector to improve sector performance, smallholders are often characterized as the Achilles heel of the oil palm sector due to poor practices and low yields compared to companies. However, ‘oil palm smallholders’ is a container concept and there has been only limited research into smallholder diversity beyond the organised versus independent farmer dichotomy. This research delves into the implementation of Good Agricultural Practices (GAP) among seven types of independent smallholders in Rokan Hulu regency, Riau province. The research area consisted of a relative established agricultural area on mineral soils and a relative frontier, mostly on peat. Smallholder types ranged from small local farmers to large farmers who usually reside in urban areas far from their plantation and regard oil palm cultivation as an investment opportunity. The underlying hypothesis is that larger farmers have more capital and therefore implement better agricultural practices than small farmers, who are usually more cash constrained. A wide range of methods was applied, including farmer and farm surveys, remote sensing, tissue analysis and photo interpretation by experts. These methods provided data on fertilizer use, nutrient conditions in oil palms, planting material, planting patterns, and other management practices in the plantations. Results show that yields are poor, implementation of GAP are limited and there is much room for improvement among all farmer types. Poor planting materials, square planting patterns, and limited nutrient applications were particularly prevalent. This implies that farmers across different typologies opt for a low-input low-output system for a myriad of reasons and that under current conditions, initiatives such as improving access to finance or availability of good planting material alone are unlikely to significantly improve the productivity and sustainability of the smallholder oil palm sector.